Markers of oxidative stress during post-COVID-19 fatigue: a hypothesis-generating, exploratory pilot study on hospital employees - Hofmann, Hanna; Önder, Alexandra; Becker, Juliane; Gröger, Michael; Müller, Markus M.; Zink, Fabian; Stein, Barbara; Radermacher, Peter; Waller, Christiane (Frontiers in Medicine, 2023)
Post-COVID fatigue is common after recovery from COVID-19. Excess formation of reactive oxygen species (ROS) leading to oxidative stress-related mitochondrial dysfunction is referred to as a cause of these chronic fatigue-like symptoms. The present observational pilot study aimed to investigate a possible relation between the course of ROS formation, subsequent oxidative stress and post-COVID fatigue.Method: 21 post-COVID-19 employees of the General Hospital Nuremberg suffering from fatiguelike symptoms were studied during their first consultation (T1: in average three months after recovery from COVID-19), which comprised an educational talk on post-COVID symptomatology and individualized outpatient strategies to resume normal activity, and 8 weeks thereafter (T2). Fatigue severity was quantified using the Chalder-Fatigue-Scale together with a health survey (Patient-Health-Questionnaire) and self-report on well-being (Short-Form-12 Health-Survey). We measured whole blood superoxide anion (O2• ‾) production rate (electron spin resonance, as a surrogate for ROS production) and oxidative stress-induced DNA strand-breaks (single cell gel electrophoresis: "tail moment" in the "comet assay").Results: Data is presented as Mean±SD or Median (interquartile range) depending on data distribution, differences between T1 and T2 were tested using a paired Wilcoxon rank sign or t-test. Fatigue intensity decreased from 24±5 at T1 to 18±8 at T2 (p<.05), which coincided with reduced O2• ‾ formation (from 239±55 to 195±59 nmol/sec; p<.05) and attenuated DNA damage (tail moment from 0.67(0.36-1.28) to 0.32(0.23-0.71); p=.05.) Discussion: Our pilot study shows that post-COVID fatigue coincides with i) enhanced O 2 • ‾ formation and oxidative stress, which are ii) reduced with attenuation of fatigue symptoms.